2015
DOI: 10.1111/pcmr.12430
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic Piper amide derivative NED‐180 inhibits hyperpigmentation by activating the PI3K and ERK pathways and by regulating Ca2+ influx via TRPM1 channels

Abstract: Piper amides have a characteristic, unsaturated amide group and exhibit diverse biological activities, including proliferation and differentiation of melanocytes, although the molecular mechanisms underlying its antimelanogenesis effect remain unknown. We screened a selected chemical library of newly synthesized Piper amide derivatives and identified (E)-3-(4-(tert-butyl)phenyl)-N-(2,3-dihydrobenzo[b][1,4]dioxin-6-yl)acrylamide (NED-180) as one of the most potent compounds in suppressing melanogenesis. In muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…MITF gene expression is regulated by many factors, including CREB, PI3K/AKT (Chae et al, ; Hwang et al, ), GSK3β (Shin et al, ), and MAPK (ERK, c‐Jun N‐terminal kinase, and p38; Peng et al, ). In our study, ERK phosphorylation was increased by PA and EP treatment, which corresponded to a decrease in MITF protein level and an increase in ROS generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MITF gene expression is regulated by many factors, including CREB, PI3K/AKT (Chae et al, ; Hwang et al, ), GSK3β (Shin et al, ), and MAPK (ERK, c‐Jun N‐terminal kinase, and p38; Peng et al, ). In our study, ERK phosphorylation was increased by PA and EP treatment, which corresponded to a decrease in MITF protein level and an increase in ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PKA/CREB signaling pathway, MITF expression and activity are regulated by extracellular signal‐regulated kinase (ERK), a mitogen‐activated protein kinase (MAPK) family member (Peng, Lin, Wang, Shih, & Chou, ) that phosphorylates MITF at S73 and targets the protein for degradation by the proteasome (Lee, Lee, Chang, & Lee, ; Wu, Lin, Yang, Weng, & Tsai, ). Phosphoinositide 3‐kinase (PI3K)/AKT (Chae et al, ; Hwang et al, ) and glycogen synthase kinase 3 beta (GSK3β; Shin et al, ) also negatively regulate MITF activity and thereby suppress melanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in the comparison to α-MSH-treated cells are expressed by the symbols # , ## , ### , and #### as p < 0.05, p < 0.01, p < 0.001, and p < 0.0001, respectively Because luteolin 7-sulfate showed a strong inhibitory effects on tyrosinase activity induced by α-MSH and forskolin, mRNA expression of tyr and mitf was also found to be downregulated when luteolin 7-sulfate was added to cells with forskolin [15]. In addition, Piper amides have been found to have antimelanogenic activity through the regulation of the TRPM1 calcium channel [35]. A recent study using HepG2 cells reported that PL is a potent activator of AMP-activated kinase [36].…”
Section: Resultsmentioning
confidence: 94%
“…In mammalian skin, melanins are transferred within melanosomes through melanocytic dendrites to epidermal keratinocytes, which gives rise to the observed pigmentation, and it has been reported that dendrite formation is promoted by increases in intracellular Ca 2+ in human melanocytes . Pigmentation can be regulated by Ca 2+ influx via a transient receptor potential cation channel: the TRPM1 channel, the downregulation of which has been correlated with a higher metastatic risk of skin melanoma . Based on the results of the Rhod‐3 calcium imaging kit, the Ca 2+ influx was observed to be greater in melanocytes overexpressing SYT4.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting finding, SYT4 interacted with ERK and positively regulated p‐ERK expression. The ERK signalling pathway may negatively affect the melanogenesis induced by the p53‐POMC‐MC1R signalling cascade to enhance the phosphorylation levels of ERK1/2 and CREB . CREB activates the transcription of MITF, which consequently triggers the transcription of the downstream melanogenic genes TYR, TYRP1, and DCT, causing increases in the melanin content.…”
Section: Discussionmentioning
confidence: 99%